A szláv nyelvfejlődés Trubeckoj-féle korszakolása és a magyar szlavisztika - Zoltán András; Золтан Андраш; Zoltan Andras (Magyar Nyelvtudományi Társaság, 2020)
Abstract. Nikolai Trubetzkoy’s periodization of the history of Slavic languages, taking the end of the Common Slavic period to be in the 12th century, was known after the second world war, under the Soviet occupation of Hungary. It could be mentioned in university lectures and in textbooks, but it was rejected by Hungarian philologists without any argumentation. The author of the article supposes that the behavior of the Hungarian Slavists was determined in this respect, too, by the official attitude of the Soviet Union to the emigré Prince Trubetzkoy.

Az orosz szellemi elit számon tartotta Trubeckoj munkásságát, s a cenzúra felpuhulásával már nyíltan is hivatkozhatott rá. Nehéz bizonyítani, de gyanítható: abban, hogy Trubeckoj (és az őt követő Durnovo) nézetei a rendszerváltozás előtti Magyarországon nem kaptak szélesebb körű publicitást, vezető szlavistáink hagyománytisztelete mellett a „nagy testvér” érzékenységére figyelő politikai óvatosság is szerepet játszhatott.
Trubetzkoy’s periodization of the development of Slavic languages and Slavic studies in Hungary
http://real.mtak.hu/108527/1/Zoltan_MNy_20-1.pdf
Keywords: Trubeckoj; ősszláv; korszakolás; a szlavisztika története Magyarországon